STRATEGI KEBIAKAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PEMBINAAN PROFESIONALISME GURU - ANDI MUHAMMAD ALIFUDDIN; NURLINDA NURLINDA; NURUL INDAR DEWI (JURNAL MAPPESONA, 2020)
The results of this study can be concluded that: (1) Principal's policy strategy in fostering teacher professionalism is very good, such as the principal conducting sharing, the teacher is included in the training. (2) Teacher professionalism competence is very good, for example in addition to the teachers teaching during class hours also the addition of class hours outside of class hours so that the results are also satisfying as in graduation. (3) Inhibiting factors in fostering professionalism of teachers are the lack of school facilities and infrastructure, and supporting factors for the existence of kinship among school members, and there are two factors that can support and inhibit the principal's policy strategy in fostering teacher professionalism, namely from internal and external factors.